A mindfulness-based intervention for Substance Use Disorder in a Brazilian vulnerable population: a feasibility mixed method study - Mayra Pires Alves Machado; Emérita Sátiro Opaleye; Andre Bedendo; Andre Bedendo; Sarah Bowen; Ana Regina Noto (Frontiers Media S.A., 2024)
IntroductionSubstance Use Disorder (SUD) is a chronic condition that impacts various facets of an individual's life, and society as a whole. The Mindfulness-Based Relapse Prevention (MBRP) protocol is an innovative intervention that can help to prevent relapse, particularly when used as a post-treatment approach. However, although there is significant evidence of its effectiveness in studies from high-income countries (HICs), there is a dearth of studies examining its feasibility and efficacy in low- and middle-income countries (LMICs). Thus, this study investigates the feasibility of MBRP as an adjunct to outpatient treatment for SUD in a socially vulnerable Brazilian population.MethodsThe study employed a mixed-methods design in eight Psychosocial Care Centers for Alcohol and Drugs (CAPS-ad) in the city of São Paulo, and involved 140 participants, 24 healthcare professionals and 7 CAPS-ad managers. In total, 17 MBRP intervention groups were conducted. The study assessed qualitative indicators of acceptability, demand, implementation, adaptation, integration, and limited efficacy testing through group interviews, in-depth interviews and field diary records. It also included limited efficacy testing of the protocol using a quantitative pre-post pilot study to investigate consumption behavior, using the Timeline Followback (TLFB) assessment method; depression, using the Center for Epidemiologic Studies Depression (CES-D) scale; anxiety, using the state trait anxiety index (STAXI-2); craving, using the Penn Alcohol Craving Scale (PACS); readiness to change, using the Readiness-to-Change Ruler (RCR); and severity of dependence, using the Severity of Dependence Scale (SDS). The qualitative data were triangulated with the quantitative data to comprehensively evaluate the feasibility of the intervention.ResultsThe sample comprised socially vulnerable participants with a high dropout rate, primarily due to social factors. Despite facing challenges in respect of regular engagement and initial cultural misperceptions of meditation, the intervention showed positive acceptance and mental health benefits, including impacts on consumption behavior.DiscussionThe study emphasizes the importance of adapting the format of the protocol to better suit vulnerable populations, and to ensure its effective integration into the public healthcare system. Future research should explore protocol modifications, assess its effectiveness in different contexts, and conduct cost-benefit analyses for broader implementation.